Kinetic simulation of steam reforming of methanol with CO formation - Ye Lwin; Saiful Azhar Saad; Khairul Nizar Ismail; Mohd Irfan Hatim (Nanyang Technological University, 2008)
Organized by Nanyang Technological University, 3rd - 5th December 2006 at Nanyang Technological University, Singapore.